Tissue Stiffness is Not Related to Pain Experience: An Individually Controlled Study in Patients with Chronic Neck and Back Pain. (23rd December 2019) - Lederer, Ann-Kathrin; Maly, Christian; Weinert, Tomas; Huber, Roman
Abstract : Background . Massage therapies such as cupping are often applied in patients with chronic neck and back pain with the assumption that they can reduce increased tissue stiffness and, therefore, improve pain. The aim of this study was to clarify whether tissue stiffness is related to pain experience in patients with chronic (>3 months) back and neck pain and whether it can be altered by a cupping massage. Methods . The tissue stiffness of the point of subjectively felt maximum pain intensity of 40 patients with neck ( n = 20) or lower back pain ( n = 20) was measured by a myometer. Exact contralateral side served as an individual control. Side of higher stiffness was then treated with a cupping massage. 5, 10, 15, and 20 minutes as well as 24 hours after treatment, tissue stiffness was measured again. Patients rated their pain on a standardized pain questionnaire (neck pain disability score (NDI) or Oswestry disability index (ODI), respectively) before and 24 hours after treatment. Results . Compared to the contralateral control side, the more painful side did not exhibit an increased stiffness of myofascial tissue before treatment (p = 0.827 ). The tissue stiffness and the side difference between treated and nontreated control sides decreased significantly after cupping (p = 0.002 and p = 0.001, respectively) but returned to baseline after 24 hours. NDI and ODI scores significantly decreased 24 hours after cupping (NDI: p = 0.012, ODI: p = 0.002 ). Conclusion . Tissue stiffness might not be related to pain experience in patients with chronic neck and lower back pain. Trial registration: German Clinical Trial Register (DRKS00011281 ).